Unraveling the underlying factors SCulPT-ing cyberbullying behaviours among Malaysian young adults - Balakrishnan, Vimala (Elsevier, 2017)
Investigating factors that drive people to cyberbully is critical, so that early interventions could be administered. Most cyberbullying studies were conducted in Western countries, with only a few focusing on Asia. This current study was undertaken to (i) design a cyberbullying behavioral model, and (ii) determine the predictors for intention to cyberbully. The first objective was achieved by integrating Sociocultural-Psychology-Technology factors into a model, aptly named SculPT, which was subsequently used to address the second objective. Additionally, a further analysis was conducted to identify specific influential sub-factors based on SculPT. The methodology involves a mixed method approach, namely focus groups and online questionnaire surveys. Three hundred and ninety nine respondents between 17 and 36 years old (M = 22.03, SD = 2.77) were recruited. Path modeling analysis revealed SculPT to predict approximately 83% of cyberbullying perpetration. All the predictors were found to have significant direct effects on intention to cyberbully, with Sociocultural having the strongest impact, followed by Technology and Psychology. A more in-depth analysis revealed five sub-factors to significantly predict cyberbullying intentions, namely Social Influence and Social Acceptability (Sociocultural), Availability and Ease of Use (Technology), and Entertainment (Psychology). Results generally concur with previous studies, and comparisons were made where appropriate. We conclude that cyberbullying prevalence still exists among young adults in the country, and with the revelation of factors behind cyberbullying, respective authorities could focus on the identified factors to help mitigate cyberbullying behaviors.